Using physical examinations to estimate age in elementary school children: A Chinese population-based study - Lei Shi; Fan Jiang; Fengxiu Ouyang; Jun Zhang; Xiaoming Shen (Elsevier, 2017)
Background: Designing a simple and accessible approach to age estimation in children and youth is a great challenge in the fields of sports and physical activity (PA). This study was designed to develop and validate a physical-examination-based method of estimating age in young children. Methods: In a cross-sectional study conducted in 2014, we performed physical examinations and assessed PA among 14,970 elementary school children 7-12 years old in Shanghai, China. Additional biological information on the children's height and birth date was ascertained through their parents. Two indicators were applied to develop a gender-specific age estimation equation: The percentage of predicted mature height (PPMH) and the Tanner stage. The equation was validated through a k-fold cross-validation approach. To check for estimation accuracy, the association between the discrepancy of estimated age (EA) and chronological age and PA was examined. Results: The gender-specific equations of EA were as follows: EAboy = -6.071 + 6.559 Tanner 2 + 13.315 Tanner 3 + 14.130 Tanner 4 + 0.190 PPMH - 0.071 Tanner 2 × PPMH - 0.146 Tanner 3 × PPMH - 0.155 Tanner 4 × PPMH; EAgirl = -4.524 - 1.251 Tanner 2 + 2.504 Tanner 3 + 8.752 Tanner 4 + 11.893 Tanner 5 + 0.158 PPMH + 0.017 Tanner 2 × PPMH - 0.024 Tanner 3 × PPMH - 0.087 Tanner 4 × PPMH - 0.118 Tanner 5 × PPMH. The mean absolute error was 0.60 years for boys and 0.59 years for girls. The discrepancy score was negatively and weakly associated with self-reported moderate-to-vigorous PA in both genders (rboy = -0.09, p < 0.001; rgirl = -0.12, p < 0.001). Conclusion: Findings suggest that physical examinations could provide a valid and reliable approach for estimating age in young Chinese children.